Epistemic modes in news production: How journalists manage ways of knowing in hybrid media events involving terrorist violence. (September 2022) - Uusitalo, Niina; Valaskivi, Katja; Sumiala, Johanna
In this article, we investigate the challenge of hybrid media events of terrorist violence for journalism and analyse how news organizations manage epistemic modes in such events. Epistemic modes refer to different ways of knowing, which are managed by newsrooms through journalistic and editorial practices. We draw from an empirical study of terrorism-related news production in the Finnish Broadcasting Company (Yle). Our data consist of thematic interviews ( N = 33) with Yle journalists, producers, and content managers and newsroom observations (14 days) conducted at Yle. The study investigates the data through a grounded theory approach with the aim of creating a theoretical understanding of knowledge production in hybrid media events. The results are drawn from a qualitative content analysis and close reading of the interview data, with the other data sets informing the core analysis. The article identifies seven epistemic modes of relevance to news production in hybrid media events: not-knowing, description, rumoring, witnessing, emotion, analysing and perpetrating. The modes are analysed in relation to three dimensions of crisis reporting: immediate sense-making, ritualizing and transformation back to normalcy. The article finds that although particular epistemic modes are typical to certain dimensions of reporting hybrid, disruptive media events, both the modes and the dimensions also are also merged and intermixed. This condition together with growing amounts of problematic epistemic modes of rumoring, emotion and perpetrating challenge journalists' epistemic authority in reporting hybrid media events involving terrorist violence.